Exposure Assessment of Silver and Gold Nanoparticles Generated During the Synthesis Process in a South African Research Laboratory - Masekameni, Masilu D.; Andraos, Charlene; Yu, Il Je; Gulumian, Mary (Frontiers in Toxicology, 2022)
During the synthesis of engineered nanomaterials (ENMs), various occupational exposures occur, leading to health consequences. To date, fewer exposure assessment studies focused on the ENMs synthesis processes. This study aimed to characterise and assess exposure to gold (AuNPs) and silver nanoparticles (AgNPs) during a synthesis process in a research laboratory in South Afirca. AuNPs and AgNPs synthesis processes were monitored for an hour in a laboratory using a Scanning Mobility Particle Sizer. The monitoring was conducted at a height of 1.2 – 1.5 m and 1.5 m away from the hood, assuming a 30 cm breathing circumference zone. Each synthesis process was monitored thrice to generate reliable point estimates, which were used to assess exposure over eight hours. A time-weighted average concentration was calculated and compared to the derived 8-hour occupational exposure limit for AgNPs (0.19 µg/m3) and the proposed provisional nano reference value for AuNPs (20 000 particles/cm3). The Multiple-Path Particle Dosimetry model was used to calculate the deposition and retention of both AuNPs and AgNPs. NPs emitted during the synthesis process were dominant in the nuclei (79% for AuNPs and 54% for AgNPs), followed by the Aitken (12% for AuNPs and 29% for AgNPs), with fewer particles in the accumulation mode (9.2% for AuNPs and 17% for AgNPs). AuNPs and AgNPs generated during the synthesis process were determined at 1617.3 ± 102 #/cm3 (0.046 µg/m3) and 2687 cm3 ± 620 (0.077 µg/m3), respectively. For the three exposure scenarios, none exceeded the occupational exposure limit for both AuNPs (provisional) and AgNPs. Workers in the synthesis laboratory are exposed to a concentration below the recommended occupational exposure limit for silver and the proposed provisional nano reference value for gold. However, chronic health effects may emanate due to high particle retention in the tracheal bronchial and alveolar region.